EDUCATION THROUGHOUT HISTORY: FROM ORIGINS TO CONTEMPORANEITY - de Oliveira, Jakson José Gomes; de Oliveira, Ana Lúcia Almeida; Filho, José Amadeu de Oliveira; Ferreira, Lindomal dos Santos (Seven Editora, 2024)
This article aims to present a history of education through History, it presents in a synthetic way the main characteristics of education during the various historical periods addressed here, they are: Education of Primitive Man; Education in Greece; Education in the Middle Ages; Education in the Protestant Reformation and the Counter-Reformation; Education of Bourgeois Man and Socialist Education. Who were the first teachers? How did this knowledge take place? Which classes or groups of people had the right to education? What is the character (religious, secular, public, private, state) that education assumes in the various historical periods? Who did education serve? These and other questions are addressed by provoking an opportunity to reflect on education in the past for a better understanding of education in the present. The work was carried out through bibliographic research, based on a dialectical analysis based on the historical conceptions of education of authors such as Aranha, Ponce, Manacorda, among others, which corroborate with the theoretical contribution that underlies the research.DOI: https://doi.org/10.56238/sevened2024.037-105